2021
DOI: 10.1021/acscatal.0c03791
|View full text |Cite
|
Sign up to set email alerts
|

Experiments and DFT Computations Combine to Decipher Fe-Catalyzed Amidine Synthesis through Nitrene Transfer and Nitrile Insertion

Abstract: Multicomponent reactions are attracting strong interest as they contribute to develop more efficient synthetic chemistry. Understanding their mechanism is thus an important issue to optimize their operation. However, it is also a challenging task owing to the complexity of the succession of molecular events involved. Computational methods have recently proven of utmost interest to help deciphering some of these processes and the development of integrated experimental and theoretical approaches thus appear as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
0
11
0
1
Order By: Relevance
“…Our study of the mechanism of amidine formation through MeCN insertion revealed that in similar conditions THF abolished amidine formation by blocking acetonitrile binding to 1b, thereby demonstrating that MeCN binds to the Fe catalyst. 34 To investigate whether MeCN binding is required to form imidazoline, we performed a fourth series of experiments (Table 4) in which the reaction medium was MeCN/THF mixtures of variable compositions.…”
Section: Catalytic Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study of the mechanism of amidine formation through MeCN insertion revealed that in similar conditions THF abolished amidine formation by blocking acetonitrile binding to 1b, thereby demonstrating that MeCN binds to the Fe catalyst. 34 To investigate whether MeCN binding is required to form imidazoline, we performed a fourth series of experiments (Table 4) in which the reaction medium was MeCN/THF mixtures of variable compositions.…”
Section: Catalytic Experimentsmentioning
confidence: 99%
“…Furthermore, using the same approach, we analyzed very recently the far more complex mechanism of amidination 34 combining nitrene transfer and nitrile insertion, which is especially relevant to the present purpose. Such reactivity calculations using the hybrid B3LYP functional are impracticable for catalyst 1b because of the size of the system combined to the multiplicity of spin states of both Fe.…”
Section: -28mentioning
confidence: 99%
See 3 more Smart Citations